Basic physical chemistry: the route to understanidng - Smith, E Brian (London : ICP, 2013)
This elegant book provides a student-friendly introduction to the subject of physical chemistry. It is by the author of the very successful Basic Chemical Thermodynamics and is written in the same well-received popular style. It is concise and more compact than standard textbooks on the subject and emphasises the two important topics underpinning the subject: quantum mechanics and the second law of thermodynamics. Both topics are challenging to students because they focus on uncertainty and probability. The book explains these fundamental concepts clearly and shows how they offer the key to understanding a wide range of chemical phenomena including atomic and molecular spectra, the structure and properties of solids, liquids and gases, chemical equilibrium and the rates of chemical reactions. This revised edition has enabled improvements and corrections to be made.
Appendix 1-4 290-296p.; Further reading 297-298p.; Periodic table 299-300p.; Index 301-308p.
Keywords: Energy; Molecular spectra; Electrons in atoms